The nation-building project in Iraq during the first monarchy (1921-1933) - latim, Esa (Al-Adab Journal, 2019)
Building political power, achieving integration between the components of society, and building a national national identity are basic requirements in the process of building the nation-state, and it gives the state and power firmness and stability, which are matters that were supposed to occupy an important position among the theorists of governance in the modern state of Iraq, but this was not The nature of the emergence of the Iraqi state, which was an expression of a consensus of a foreign and national will, even if the former prevailed, was achieved because the Iraqi regime, with its components (the crown, honorable officers and tribal leaders), was unable to reconcile between foreign interests, the requirements and goals of building the nation-state in the modern sense, in fact the stage of monarchy (nationalism) A new situation in Iraq has been produced, represented in the struggle between national elements under the cover of personal interests, party approaches and sectarian calculations, and created a new concept of national struggle, which is ending the domination of the bourgeois class over the interests of the people, and all of these matters are difficult to complete the institutional building of the modern Iraqi state, the goal of this The intervention is to examine the mechanisms of nation-state building in Iraq during the period of the monarchy and to dissect the nature of the relationship between power and society, and it will depend on approaches that are compatible S with the outputs of the topic, of different natures, foremost of which are the historical method, the content analysis approach, and the political system analysis approach based on the problematic that addresses the issue of nation-state building in Iraq during the royal era